Kundalini yoga as mutual recovery: a feasibility study including children in care and their carers. Issue 4 (19th December 2016) - Vallejos, Elvira Perez; Ball, Mark John; Brown, Poppy; Crepaz-Keay, David; Haslam-Jones, Emily; Crawford, Paul
Abstract : Purpose: The purpose of this paper is to test whether incorporating a 20-week Kundalini yoga programme into a residential home for children improves well-being outcomes. Design/methodology/approach: This is a mixed methods feasibility study. Feasibility was assessed through recruitment and retention rates as well as participants' self-report perceptions on social inclusion, mental health and well-being and through semi-structured interviews on the benefits of the study. Mutual recovery entailed that children in care (CIC), youth practitioners and management participated together in the Kundalini yoga sessions. Findings: The study initially enrolled 100 per cent of CIC and 97 per cent (29/30) of eligible staff. Attendance was low with an average rate of four sessions per participant (SD=3.7, range 0-13). All the participants reported that the study was personally meaningful and experienced both individual (e.g. feeling more relaxed) and social benefits (e.g. feeling more open and positive). Pre- and post-yoga questionnaires did not show any significant effects. Low attendance was associated with the challenges faced by the children's workforce (e.g. high levels of stress, low status, profile and pay) and insufficient consultation and early involvement of stakeholders on the study implementation process. Research limitations/implications: Because of the chosen research approach (i.e. feasibility study) and low attendance rate, the research results may lack generalisability. Therefore, further research with larger samples including a control or comparison group to pilot similar research questions is mandatory. Practical implications: This study has generated a number of valuable guiding principles and recommendations that might underpin the development of any future intervention for CIC and staff working in children's homes. Social implications: The concept of togetherness and mutuality within residential spaces is discussed in the paper. Originality/value: The effects of Kundalini yoga have not been reported before in any peer-review publications. This paper fulfils an identified need (i.e. poor outcomes among CIC and residential staff) and shows how movement and creative practices can support the concept of mutual recovery.